Report of a rare case of adenoid cystic carcinoma (ACC) in the breast of a 43-year-old woman - Amir Hosein Jafarian; Zahra Akhbari (Mashhad University of Medical Sciences, 2024)
Introduction: Adenoid cystic carcinoma (ACC) of the breast belongs to the basal-like subgroup of breast carcinomas. This group of tumors is triple negative and are negative for all three biomarkers, estrogen receptor (ER) and progesterone receptor (PR) and human epidermal growth factor receptor 2 (Her2). However, triple-negative appearance along with pseudo-basal features and positivity for CD117 or CK14 and CK17 expression is considered pathognomonic for ACC. Unlike other types of triple negative breast tumors, ACC has an excellent prognosis. In this report, a description of one of the cases with ACC and its histopathological features is presented. Case presentation: The patient was a 43-year-old woman who referred to our medical center with complaints of right breast pain radiating to the armpit since three months before visiting. In mammography, in the right breast, a hypoecho-solid mass with irregular borders in the subareolar region was reported with a retracted nipple. In the ultrasound, the presence of a white hypochoic mass with irregular boundaries was confirmed. In histological evaluation, plates of malignant cells with distinct atypia were reported. The sample was evaluated by immunohistochemistry (IHC) and the evaluation was negative for the expression of the three markers ER, PR and Her2, but positive for the expression of the CD117 marker, and accordingly, the diagnosis of ACC was confirmed for the patient. Conclusion: ACC tumors are characterized by a triple-negative appearance with basal-like features and positivity for CD117 or cytokeratins 14 or 17 expression that according to this patter, it is very important to distinguish ACC from other tumors with worse prognosis.